DIGITAL TECHNOLOGY MEDIATES BUSINESS STRATEGIES AND JOB CREATION LAW TO MSME PERFORMANCE IN THE CULINARY SECTOR - Setiawan, Hery; Santy, Yuyu Jahratu Noor; Fitriyani, Zenita Afifah; Huda, Khasbulloh (Jurnal Ilmiah Manajemen, Ekonomi, & Akuntansi (MEA), 2023)
The purpose of this study is to determine the direct and indirect influence on the business strategy variables and the Job Creation Law variable on the MSMEs Performance in the culinary sector which is mediated by the Digital Technology variable. The research method used is a quantitative method using the SmartPLS 3.2.8 program in analyzing the data, so that it can identify the relationship between variables. The research population is MSMEs in the culinary sector in Prajurit Kulon sub-district. By using the Slovin formula, a sample result of 83 was obtained. The data collection techniques used were observation, interviews and questionnaires. Data analysis was carried out using outer model test, innerl model test, and hypothesis test.The results of the study are suspected to have a direct influence on the variables of business strategy and the Job Creation Law on the Performance of MSMEs in the Culinary Sector mediated by digital technology. This research is expected to help improve the performance of MSMEs in the culinary sector in the Prajurit Kulon district, Mojokerto City, and can be a reference and study for research on digital technology that mediates business strategies and the Job Creation Law on MSME performance.